Output filter implementation for digital waveguide clarinet model - MŁYŃSKA, Aleksandra (Archives of Acoustics, 2008)
The modification of a dynamic physical clarinet model based on a digital waveguide is presented in the paper. In particular, the influence of the output filter parameters on the signals generated by the model was investigated. As the output filter, the adaptive filter was designed and implemented with various parameter values for different reference signals. The recorded clarinet sound samples and the signals generated by the clarinet model were compared.